Tindak Tutur Ilokusi Asertif, Direktif, Ekspresif, Komisif, dan Deklaratif pada Program Gelar Wicara Mata Najwa - Artati, Artati; Wardhana, Dian Eka Chandra; Basuki, Rokhmat (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research was to describe the assertive, directive, expressive, commissive, and declarative illocutionary speech acts on the December 2018 Mata Najwa talk show program. The research method used is descriptive qualitative method. Data collection techniques using documentation techniques obtained from the Mata Najwa video program December 2018 edition taken using a handphone. Data analysis techniques are done by reducing data, presenting data, interpreting data, and conclusions. Test the validity of the data by validating pragmatic experts and member checks. The type of illocutionary speech acts in the Mata Najwa talk show program mostly use expressive speech acts that contain congratulations, thanks, praise, and criticism. Assertive speech acts aim to say, report, and mention. The directive speech acts contain speech of asking, asking, demanding, suggesting, and opposing. Commissive speech acts contain speech promising, swearing, and threatening. Then, declarative speech acts contain speech deciding, canceling, prohibiting, permitting, and forgiving. From the results of this study, it shows that in making talk show programs it is better to use variations in illocutionary speech acts and the most dominant percentage of their use should use expressive speech acts so that events are more interesting.